Analisa Tren dalam Mengevaluasi Kinerja Rasio Keuangan Pt. Gudang Garam Tbk (GGRM) Selama Periode 2020-2023 - Bambang Widjanarko Susilo; Benny Cuaca; Edy Susanto; Ayu Miranti Kusumaningrum; Galuh Aninditiyah; Rezky Eko Prasetyo; Zahra Dinul Khaq; Vivi Kumalasari Subroto; Sri Wahyuning; Febryantahanuji Febryantahanuji (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Based on the financial performance analysis of PT. Gudang Garam Tbk (GGRM) during the 2020–2023 period, the company faced significant challenges that impacted its financial condition. One of the main factors affecting the company's performance is the increase in tobacco excise duties, which has affected the cost structure and selling prices of its cigarette products. Additionally, the increasing regulatory pressure and changes in consumer behavior have posed unavoidable challenges. The decline in profitability and liquidity ratios, such as Return on Assets (ROA) and Current Ratio (CR), indicates the negative impact of these external conditions on the company’s ability to generate profit and meet short-term obligations. This decline suggests that the company is struggling to balance income and operational costs. The fluctuating solvency ratio also raises concern. Although the company manages to maintain a balance between debt and equity, these fluctuations show challenges in managing long-term assets and liabilities. Dependence on debt and rising operational costs pose risks to the company's financial stability. These fluctuations affect the company's ability to maintain liquidity and solvency in an increasingly competitive market. Trend analysis from the financial statements indicates that the company needs to strengthen its adaptation strategies and risk management to face the growing market challenges. GGRM must focus on product innovation and marketing strategies that can attract new customers while retaining existing ones. Furthermore, the company must adapt to changing regulations and evolving consumer trends. The results of this study provide important insights for stakeholders regarding the financial condition of the tobacco industry. In this challenging situation, GGRM must continue to develop more adaptive strategies to survive and thrive amidst the dynamic market and increasingly stringent regulations.